Imagining Venetian Hydro-Peripatetics with Ciardi, Favretto, Lansyer, and Pasini - Finch-Race, Daniel A. (Lagoonscapes, 2021)
This article proposes a sensory approach to physical and representational environments based on a pedestrian perspective. With a view to bringing arts-based considerations to bear on UN Sustainable Development Goal 6.6, concerned with the protection and restoration of water-related ecosystems, the analysis primarily revolves around Italian and French depictions of Venice in the 1880s-1890s that encompass stimuli for smell, sound, taste, and touch as much as sight. Close readings are undertaken to highlight hyperlocal elements that merit consideration when determining courses of action for the long-term good of the lagoonscape.